The Communication Ability with Sign Language by Teachers Towards the Achievements of Special Needs Children who are deaf. - Rindang, Adelia; Yeni, Putri; Fitriani, Wahida; Kiat, Ton (Yayasan Minang Darussalam, 2024)
This research demonstrates the importance of sign language as an effective communication tool for the deaf, particularly in the educational context at SLB Negeri 1 Pagaruyuang. It also emphasizes the significance of developing communication methods that enhance better accessibility for students with special needs to comprehend lesson materials and actively participate in the learning process. Utilizing a descriptive method with a qualitative approach to describe the communication patterns developed by these deaf teachers. Teachers teaching these students need to integrate spoken language with body language, face challenges in understanding deaf students in particular, and often receive assistance from fellow teachers to facilitate better understanding.